Variabilidade morfométrica e molecular em Desmodus rotundus (Chiroptera, Phyllostomidae) de diferentes áreas de risco para raiva rural no estado do Pará, Brasil - ANDRADE, Fernanda Atanaena Gonçalves de (Universidade Federal do Pará, 2017)
At the present study the hypothesis of population morphological and molecular heterogeneity was tested in several groups of the common vampire bat Desmodus rotundus from oriental Amazonia as well the relationship among the environmental heterogeneity and the process and patterns of rabies outbreaks in human and bovine population was described. For this 776 individuals of common vampire bats from 72 different places of state of Pará were disposed by Instituto Evandro Chagas (IEC - Ministério da Saúde/Belém), Laboratório Nacional Agropecuário (Lanagro/Belém) and Fundação de Vigilância em Saúde do Amazonas (FVG/Manaus). Data from 1999 to 2008 of rabies upon humans and bovines in Pará were disposed by the Secretaria Executiva de Saúde Pública do Pará (SESPA). For morphometric analysis, 39 phenotypic measures (16 bodies and 23 cranials) all adult individuals (329 males and 315 females) were obtained. For genetic analysis, 258 bats (47% males and 53% females) were characterized by 10 microsatelite markers. To describe the areas of rabies risk we used the ecological, biological and socioeconomic shapes of environment as well the soil using, all these geographically georeferenced. One of our results of phenotypic inferences suggest that vampires from Pará showed the tendency to group formation with individuals of the north region of state (Amazonas basin, Marajóand Northeastern regions), only as well they were less similar to bats from southern and southwestern regions. In general, D. rotundus did not show high phenotypically structure among the groups in Pará. The highest variability occurrence in D. rotundus, was not observed among geographic groups. According to molecular analysis of variance (AMOVA), 96% of them were found within each studied group. Our data showed that several of the groups studied in Pará are still under Hardy-Weinberg equilibrium, suggesting the existence of one single panmitic population of the common vampire bat in this North state, but with tendencies to the formation of three great groups (Amazon basin, Marajóand Northeast). To this panmitic population, the reproduction and adaptation patterns garanteed the high equity of allelic richness and good rates of genetic diversity in D. rotundus from oriental Amazon, even under the fragmentation effects in many areas of Pará state, mainly in the east side.